The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1103/physrevb.78.035409
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the adsorption characteristics of water on Ru{0001} with preadsorbed oxygen

Abstract: The coadsorption of water and preadsorbed oxygen on Ru͕0001͒ was studied by synchrotron-based highresolution x-ray photoelectron spectroscopy. A dramatic change was observed in the interaction of water with oxygen between low and high oxygen precoverages. Low oxygen coverages below 0.18 ML induce partial dissociation, which leads to an adsorbed layer of H 2 O and OH. Around half the oxygen atoms take part in this reaction. All OH recombines upon heating to 200 K and desorbs together with H 2 O. Oxygen coverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 39 publications
(72 reference statements)
4
42
0
Order By: Relevance
“…In particular, the behavior found for the O͑2 ϫ 2͒ / Ru͑0001͒ seems to agree with the experimental observation that coadsorption of small amount of oxygen with water on Ru͑0001͒ enhance the dissociation of water. 2,6 Besides the effect of the adsorbed oxygen on the energetics of the dissociation products studied in Ref. 12, one could argue that the presence of oxygen is likely to favor the presence of buckled structures similar to the water dimer studied here and reminiscent of the bilayer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the behavior found for the O͑2 ϫ 2͒ / Ru͑0001͒ seems to agree with the experimental observation that coadsorption of small amount of oxygen with water on Ru͑0001͒ enhance the dissociation of water. 2,6 Besides the effect of the adsorbed oxygen on the energetics of the dissociation products studied in Ref. 12, one could argue that the presence of oxygen is likely to favor the presence of buckled structures similar to the water dimer studied here and reminiscent of the bilayer.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental observation that the presence of preadsorbed oxygen, at low coverage, on Ru͑0001͒ promotes the dissociation of water can support this interpretation. 2,6 B. Role of the water-metal interaction…”
Section: A Water Dimer On O(2 ã 2) õ Ru(0001)mentioning
confidence: 99%
See 1 more Smart Citation
“…19-21͒ on the p͑2 ϫ 1͒ oxygen covered ruthenium surface. The XPS experiments of Gladys et al 1 showed that between 170 and 180 K most of the water desorbs intact from the surface and that the binding energy of the O 1s peak of the remaining water changed by 0.6 eV, indicating the formation of a second water species H 2 O͑2͒. Recently, Shavorskiy et al 22 reported that the intact water species adsorbed on the O͑2 ϫ 1͒ / Rh͑111͒ surface between 160 and 190 K have the same spectroscopic signature in XPS as the one observed for higher oxygen coverage on Ru͑0001͒.…”
Section: Introductionmentioning
confidence: 99%
“…15͒ prevents any long-range ordering in the water overlayer. Recently, Gladys et al 1 performed an x-ray photoelectron spectroscopy ͑XPS͒ and nearedge x-ray absorption spectroscopy ͑NEXAFS͒ study of water adsorption on the O͑2 ϫ 1͒ / Ru͑0001͒ surface. They reported that water adsorbs intact at 140 K and no indication of dissociation was observed at higher temperatures near the point of desorption.…”
Section: Introductionmentioning
confidence: 99%